Magnetic resonance imaging of presumptive neonatal encephalopathy in a foal. (6th May 2016) - Wong, D. M.; Jeffery, N.; Hepworth‐Warren, K. L.; Wiechert, S. A.; Miles, K.
Summary: A 10‐h‐old Thoroughbred foal presented with clinical signs consistent with neonatal encephalopathy including absent suckling behaviour, lack of affinity for the mare and seizures. The foal was provided supportive care and treated with broad‐spectrum antimicrobials and fed via naso‐oesophageal tube. In addition, magnetic resonance imaging (MRI) was performed to investigate for structural changes that might be evident with equine neonatal encephalopathy. Notable findings on MRI included hyperintensity of the basal nuclei and superficial layers of the ventral cerebral hemispheres as well as the ventral thalamic nuclei and rostral aspect of the ventral midbrain. These imaging changes were consistent with the counterpart disease in infants and are the first to document MRI changes in a foal with neonatal encephalopathy. This report serves as an initial description of MRI findings associated with the presumed diagnosis of equine neonatal encephalopathy and also serves to solicit future diagnostic imaging studies that may help elucidate the pathophysiology and prognosis of equine neonatal encephalopathy.